STROBE-X: X-ray Timing and Spectroscopy on Dynamical Timescales from Microseconds to Years - Ray, Paul; Arzoumanian, Zaven; Ballantyne, David; Bozzo, Enrico; Brandt, Soren; Brenneman, Laura; Chakrabarty, Deepto; Christophersen, Marc; DeRosa, Alessandra; Feroci, Marco; Gendreau, Keith; Goldstein, Adam; et al. (2019)
STROBE-X is a probe-class mission concept, selected for study by NASA, for X-ray spectral timing of compact objects across the mass scale. It combines huge collecting area, high throughput, broad energy coverage, and excellent spectral and temporal resolution in a single facility, enabling a broad portfolio of high-priority astrophysics.